Integration of Science and Religion Learning Approaches in the Context of Modern Education - Andi Yuyung; Arismunandar Arismunandar; Suardi Suardi; Lutfi Lutfi; Jusman Jusman (Journal on Education, 2024)
The integration of science and religion learning is becoming an increasingly relevant topic in the context of modern education. Basically, education aims to develop the intellectual, moral and spiritual aspects of learners but, in practice, science and religion education are often separated, resulting in a dualistic view that potentially hinders the formation of a holistic understanding. This article aims to explore the concept of integration between science and religion and analyse relevant approaches to its application in modern educational curricula. Using the literature review method, the article seeks to understand how the integration of science and religion can help learners develop comprehensive scientific insights, while taking into account spiritual and moral values. The conclusion of this article is that various approaches to learning science and religion in modern education can create a balance between empirical knowledge and ethical values, resulting in a generation that is both critically minded and spiritually aware.